Distribution, Local Use and Conservation Challenges of Okra (Abelmoschus Esculentus (L.) Moench) in Metekel Zone of Benishangul Gumuz Regional State, Western Ethiopia (Indian Journal of Agriculture Engineering (IJAE), 2025)
Okra is a multifunctional vegetable crop since its edible parts can be used for a variety of purposes and are consumed in large quantities in western Ethiopia. Although it is rich in nutrition and readily available in the local market, it is an underappreciated indigenous vegetable in Ethiopia. Therefore, the study aimed to assess and identify the crop potential distribution, traditional uses, and existing conservation challenges of okra (Abelmoschus esculentus) in the selected districts of Metekel Zone. Data were collected through interviews and focus group discussions, based on a semi-structured questionnaire, in the three purposively chosen districts. The respondents were purposively selected indigenous okra farmers and agriculture experts in the districts. The collected data were analysed using SPSS software version 21 and Microsoft Excel 2010. The results revealed that most respondents (46.81%) cultivate okra in their primary field, as an intercrop, and in their homestead. Most of the respondents (68.09%) cultivate okra during the monsoon, while the least of them (14.89%) do so in both seasons. Regarding its local use, all respondents agreed that okra has been used in their community both as a food ingredient in the making of soup and stew, and as a traditional Medicine. In the study areas, immature okra pods and fruit are mainly used for food purposes. 91.49% of the respondents agreed that okra has been used to treat stomach ulcers, followed by improving appetite, for the health and well-being of pregnant women, and treating constipation, with 89.36%, 87.23%, and 81.91% of respondents, respectively. 14.89% of them are using okra to heal a wound/cut on a human. A lack of knowledge among urban dwellers about the crop (68.09%), climate change (48.94%), and lower attention given by concerned government bodies were identified as the main conservation challenges of the crop. Therefore, giving due attention to research and promoting and enhancing the food value improves human nutrition and wellbeing among nearby urban consumers, and secures the conservation and sustainable use of okra in the study areas.